2012
DOI: 10.1111/j.1540-5893.2012.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

“Tort Tales” and TV Judges: Amplifying, Modifying, or Countering the Antitort Narrative?

Abstract: This article joins the debate about the popular pervasiveness of antitort and antilitigation attitudes by examining whether, and to what extent, antitort or antilitigation sentiment is present in the narratives about law offered by reality‐based television judge shows. Given the persistent debate about tort reform and scholars' recognition of the role played in this debate by simplified narratives about the legal system, we analyze whether reality‐based TV judge shows as a genre contribute to the creation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Prior work has found that the public's primary source of information about the legal system is the news media (Yankelovich & White, Inc., 1978) and that television and other entertainment programming also play a role (Wilson & Ackerman, 2012). Although it is easier to think of entertainment portrayals of trials, there are also notable instances of settlements, for example, Erin Brockovich (Soderberg, 2000).…”
Section: Systemic Implications Of Settlement Schemasmentioning
confidence: 99%
“…Prior work has found that the public's primary source of information about the legal system is the news media (Yankelovich & White, Inc., 1978) and that television and other entertainment programming also play a role (Wilson & Ackerman, 2012). Although it is easier to think of entertainment portrayals of trials, there are also notable instances of settlements, for example, Erin Brockovich (Soderberg, 2000).…”
Section: Systemic Implications Of Settlement Schemasmentioning
confidence: 99%
“…Examples of the impact of popular culture on legal consciousness abound. For example, "tort tales", TV judge shows, and crime dramas have figured prominently in debates about legal issues (Haltom and McCann 2004;Elkins 2007;Wilson and Ackerman 2012;Tyler 2006). Depictions of crime shape the social construction of criminality and legality (Mason 2003).…”
Section: Legal Consciousness: Popular Representations Of Crime and Trmentioning
confidence: 99%
“…Compare the interesting studies of representation on the American court TV shows Judge Judy, Judge Joe Brown and The People's Court byKohm (2006); andWilson and Ackerman (2012).…”
mentioning
confidence: 99%